2017
DOI: 10.1111/radm.12283
|View full text |Cite
|
Sign up to set email alerts
|

Industry cognitive distance in alliances and firm innovation performance

Abstract: This paper focuses on the role of industry cognitive distance in innovation alliances on firm innovation performance. Drawing from the literature on technological cognitive distance in alliances, we elaborate on the role of industry cognitive distance between partners and its impact on managerial attention to investigate the role of numbers of alliances of low (intra-industry) and high (inter-industry) industry cognitive distance on firm innovation performance. Intra-industry alliances offer lower opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 97 publications
(183 reference statements)
2
34
0
Order By: Relevance
“…Meanwhile, grounding on the knowledge-based view, they also pointed out that industrial diversity provides knowledge access benefits, which may promote firm innovation. Considering that, they proposed a U or inverted U correlation between alliance network industrial diversity and firm innovation [26,30,40,41] and verified it empirically.…”
Section: Alliance Network Industrial Diversity and Innovation Ambidexmentioning
confidence: 98%
See 4 more Smart Citations
“…Meanwhile, grounding on the knowledge-based view, they also pointed out that industrial diversity provides knowledge access benefits, which may promote firm innovation. Considering that, they proposed a U or inverted U correlation between alliance network industrial diversity and firm innovation [26,30,40,41] and verified it empirically.…”
Section: Alliance Network Industrial Diversity and Innovation Ambidexmentioning
confidence: 98%
“…Previous scholars have found that the utilization of external knowledge depends on organizational learning and absorptive capacity [39] and partners from the same industry with high technological similarity, familiar routines, and cooperation synergies can more easily integrate knowledge [26,40]. Driving from transaction cost theory, most scholars argued that alliance network industrial diversity might cause resource misfits or lack of synergies, which may increase the collaboration difficulties and impede the alliance performance.…”
Section: Alliance Network Industrial Diversity and Innovation Ambidexmentioning
confidence: 99%
See 3 more Smart Citations